Efektifitas Atraktan terhadap Lalat Buah Belimbing di Jawa Timur - SODIQ, MOCH; SUDARMADJI, SUDARMADJI; SUTOYO, SUTOYO (Agrotrop : Journal on Agriculture Science, 2016)
Effectiveness of Attractants to Star Fruit Flies in East Java. Fruit flies have become one of the important pests in plants carambola (Averrhoa carambola L.). In order to overcome the attack of fruit flies, always wrap the fruit growers and install attractant methyl eugenol atcarambola crop during the flowering plants to the star fruit is harvested, but the results are not optimal in controlling fruit flies, making it necessary to find other ways to control the star fruit flies were more effective. The research objective was to test the effectiveness of a combination of substances towing / attractants, feeding stimulants odor, color and volume to a fly attractant a star fruit. Research was conducted on land farmers in Blitar and Tuban. As for knowing the type of fruit flies that attack the star fruit, be identified in laboratory Plant Pests. Research using completely randomized design and each treatment was repeated 4 times. Parameters measured were the type, number, and trapped fruit fly sex attractant. Results of the study is a combination of the type of attractant M. bracteata, stimulating smell of guavajuice feed, as well as yellow and a volume of 1.5 ? most effective attractant to lure star fruit fly males and females. The fruit flies were trapped only one type that is Bactrocera carambolae.
Keywords: Effectiveness; attractants; Fruit Flies